2011
DOI: 10.4028/www.scientific.net/amr.189-193.1401
|View full text |Cite
|
Sign up to set email alerts
|

Press Forging of Thin-Walled AZ31 Magnesium-Alloy Components

Abstract: The press forging of AZ31 magnesium-alloy sheets for producing thin-walled structural components used in the electronics industry was examined by both the finite element analysis and the experimental approach in the present study. The experimental results obtained from the compression tests and ring compression tests were employed in the finite element simulations to investigate the effects of process parameters, such as forming temperature, friction condition, embossment location, and sheet thickness on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…As an replacement for Zr, Xin Guangshan et al [3] developed a new high-strength Mg-Zn-Mn alloy with high zinc content, namely ZM61 alloy, on the basis of ZM21. Mg-xZn-1Mn (x=4, 5,6,7,8,9) alloys were also examined in Chongqing University [4,5]. By adding 1-3% Al to ZM61 alloy, S. S. Park et al found that the addition of Al element could refine the microstructure of the alloy and lead to changes in the types of dispersion particles [6], however, when a large amount of Al was added to ZM61 alloy, the coarse Mg21(Al, Zn)17 phase is formed in the microstructure of ZM61-3%Al alloy, which greatly reduces the toughness of the alloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an replacement for Zr, Xin Guangshan et al [3] developed a new high-strength Mg-Zn-Mn alloy with high zinc content, namely ZM61 alloy, on the basis of ZM21. Mg-xZn-1Mn (x=4, 5,6,7,8,9) alloys were also examined in Chongqing University [4,5]. By adding 1-3% Al to ZM61 alloy, S. S. Park et al found that the addition of Al element could refine the microstructure of the alloy and lead to changes in the types of dispersion particles [6], however, when a large amount of Al was added to ZM61 alloy, the coarse Mg21(Al, Zn)17 phase is formed in the microstructure of ZM61-3%Al alloy, which greatly reduces the toughness of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, squeeze casting the Mg-6Zn-0.1Ca-0.5Mn alloy under 95MPa pressure and T6 heat treatment resulted in a tensile strength of 300 MPa, a yield strength of 180 MPa, and an elongation of 10%, which were 122%, 62% and 32% higher than gravity casting respectively [8]. Since the Hall-Petch constant of magnesium is 280MPa•m 1/2 , which is more than 4 times that of aluminum (68 MPa•m 1/2 ) [9], fine crystal has a very significant strengthening effect on Mg-Zn alloy. In this paper, the evolution of microstructure and mechanical properties of Mg-6Zn alloy microalloyed with different contents of Al element during squeeze casting and extrusion deformation were examined to explore the mechanism of high strength and high toughness of magnesium alloy, so as to provide a technical solution for producing highly efficient magnesium alloys at a reasonable cost.…”
Section: Introductionmentioning
confidence: 99%
“…However, the strength, toughness, creep resistance, and other properties of magnesium alloys are lower than those of other metal materials. Therefore, the wide application and actual production of magnesium alloys is greatly restricted [4,5]. According to Zhang et al [6], the mechanical properties and formability of magnesium alloys are improved via plastic deformation and heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium alloy is one of the most widely used lightweight structural materials because of its low density, high specific strength and specific stiffness [1,2]. In addition, magnesium and its alloys have a series of advantages, such as strong electromagnetic interference resistance, excellent machining performance, and fine damping performance, good thermal conductivity, and easy recovery and so on.…”
Section: Introductionmentioning
confidence: 99%